2022
DOI: 10.3389/fpsyg.2022.935342
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of turn-taking in sign language conversations: An overview of language modality and turn structure

Abstract: The task of transitioning from one interlocutor to another in conversation – taking turns – is a complex social process, but typically transpires rapidly and without incident in conversations between adults. Cross-linguistic similarities in turn timing and turn structure have led researchers to suggest that it is a core antecedent to human language and a primary driver of an innate “interaction engine.” This review focuses on studies that have tested the extent of turn timing and turn structure patterns in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 86 publications
0
4
0
2
Order By: Relevance
“…A new study has shown that many children participate in back-and-forth interactions with their caregivers. The more opinion they have in the brain, the more responsible they are for language production and processing (Horton & Singleton, 2022). The study also showed a strong connection between the number of turns students take in conversation and the scores they receive on the standard speaking test.…”
Section: Turn-talking Strategymentioning
confidence: 64%
“…A new study has shown that many children participate in back-and-forth interactions with their caregivers. The more opinion they have in the brain, the more responsible they are for language production and processing (Horton & Singleton, 2022). The study also showed a strong connection between the number of turns students take in conversation and the scores they receive on the standard speaking test.…”
Section: Turn-talking Strategymentioning
confidence: 64%
“…Based on the results from this in-depth observation of teacher-student interaction, our study suggests that, at least for this Deaf teacher and her aide, socialization patterns for promoting student’s visual modality capital are reminiscent of how Deaf caregivers engage with their deaf children in infancy. Overall, like Lieberman (2015) , we observe that the Deaf preschoolers from Deaf parented families seemed to already know how to engage visually and are thus “ready to learn” and appear to respond well to the teacher’s explicit and implicit (linguistic, discourse-embedded) attention prompts that support interaction in a visual language [see Horton and Singleton (2022) this volume, for a review of turntaking practices in a signed language]. These DoD students are more frequently invited to participate because it appears that they anticipated the teacher’s invitation (i.e., they were already looking at her when she was doing the inviting and could thus appropriately respond).…”
Section: Conclusion and Implication For Practicementioning
confidence: 98%
“…Adults who engage in these behaviors enable a deaf child to learn where to look for, and even anticipate, the source of signed linguistic information. More specifically, the child learns that (a) following their caregiver’s gaze will lead to meaningful information, (b) shifting their gaze back to the caregiver after object exploration will provide linguistic information, (c) gaze shifting will enable them to follow multi-party signed conversation, (d) effective visual access means no visual obstruction should be blocking the source of linguistic information, (e) movement and visual cues (perhaps later shifting into more linguistic cues) can serve as turn taking regulators [see Horton and Singleton (2022) , in this volume]. With this modality capital leveraged, a young deaf child is thus primed to acquire a language that is organized in the visual modality.…”
Section: Introductionmentioning
confidence: 99%
“…This gaze-following is not automatic, and young deaf children exposed to sign languages appear to develop the ability earlier than hearing-speaking children (Brooks et al 2020). There is also a protracted time course for the development of appropriate gaze following in signed conversations for deaf children acquiring sign languages in a classroom setting (Horton and Singleton 2022).…”
Section: The Pragmatic-interactional Function Of Eye Gazementioning
confidence: 98%